(untitled) (JURNAL PROTEKSI KESEHATAN, 2020)
Breast milk (ASI) is the only food that is the best for babies, because it has the most complete nutritionalcomposition for baby’s growth and development. Methode: this research is analytic using cross sectional approach. The sampling technique is by simple random sampling. Data analysis was performed using the Chi-Square test at a significance level of p<0.05. Result: the study showed that from 68 respondents the majority of knowledge of breastfeeding morthers with exclusive breastfeeding was well-informed 48 people (70.6%) and the ChiSquare statistical test results obtained a P value of <0.05 (P. Value = 0.004). Breastfeeding with exclusive breastfeeding the majority of positive attitude 57 people (83.8%) and the Chi-Square statistical test results obtained a value of P<0.05 (P. Value=0.008). Conclusion: based on the results of the study showed a significant relationship between knowledge (P. Value=0.004) and attitude (P. Value=0.008) towards exclusive breastfeeding.